DOZ047.83: Coordination of care through implementation of a multidisciplinary clinic for patients with esophageal atresia and tracheoesophageal fistula. (24th June 2019) - Platt, J; Mitchell, I; Bjornson, C; Bailey, J A M
Abstract: Introduction: Esophageal atresia/tracheoesophageal atresia (EA/TEF) is a multisystem congenital anomaly. Initial treatment is complex and ongoing complications are numerous. Coordination of care has been shown to reduce costs and hospitalizations in complex populations. A previous study at our center demonstrated that children with EA/TEF lacked coordinated care. A multidisciplinary clinic was established to provide coordinated care, screen for complications, provide anticipatory guidance, and improve outpatient access. Methods: This single-center retrospective cohort study included children with EA/TEF born between March 2005 and March 2011 and enrolled in the clinic. Patients with EA alone were excluded. A chart review was completed to identify demographics, hospitalizations, emergency visits, clinic visits, coordination of outpatient care, and adherence to the intended clinic schedule. Results: Twenty-five patients were included; 84% had a C-type EA/TEF. Multidisciplinary clinics had an average of 4.3 health care providers (1.75 physicians) per visit. Adherence to the visit schedule was 91.4%. The average length of stay (46.2 + 37.9 days) for the initial hospital admission was similar to the previous study cohort. Subsequent hospital admissions were reduced in number and length of stay, most notably in the first two years of life (0–1 year: 1.28 + 1.2 admissions/patient; 10.7 + 19.1 days/admission; 1– 2 years: 0.6 + 0.76 admissions/patient; 3.7 + 3.2 days/admission). Conclusions: Multidisciplinary care clinics for medically complex children such as those with EA/TEF can improve care through coordination of visits with multiple health care providers and may contribute to reduced use of acute care services.